Endothelial activation is associated with intestinal epithelial injury, systemic inflammation and treatment regimen in children living with vertically acquired HIV‐1 infection. Issue 4 (5th November 2020) - Choudhury, B; Brown, J; Ransy, DG; Brophy, J; Kakkar, F; Bitnun, A; Samson, L; Read, S; Soudeyns, H; Vaudry, W; Houston, S; Hawkes, MT
Abstract: Background: Premature development of cardiovascular disease in children living with HIV‐1 (CLWH) may be associated with compromised gut barrier function, microbial translocation, immune activation, systemic inflammation and endothelial activation. Biomarkers of these pathways may provide insights into pathogenesis of atherosclerotic disease in CLWH. Methods: This was a cross‐sectional study of CLWH enrolled in the multicentre Early Pediatric Initiation‐Canadian Child Cure Cohort (EPIC 4 ) who were on antiretroviral therapy (ART) with undetectable viral load. Plasma biomarkers of intestinal epithelial injury [intestinal fatty acid binding protein‐1 (IFABP)], systemic inflammation [tumour necrosis factor (TNF) and interleukin‐6 (IL‐6)] and endothelial activation [angiopoietin‐2 (Ang2), soluble vascular endothelial growth factor‐1 (sVEGFR1) and soluble endoglin (sEng)] were quantified by enzyme‐linked immunosorbent assay. Correlation and factor analysis of biomarkers were used to examine associations between innate immune pathways. Results: Among 90 CLWH, 16% of Ang2, 15% of sVEGFR1 and 23% of sEng levels were elevated relative to healthy historic controls. Pairwise rank correlations between the three markers of endothelial activation were statistically significant ( ρ = 0.69, ρ = 0.61 and ρ = 0.65, P < 0.001 for all correlations). An endothelial activation index, derived by factor analysis of the three endothelial biomarkers, was correlated with TNF ( ρ = 0.47, P < 0.001), IL‐6 ( ρ = 0.60, P < 0.001) and intestinal fatty acid binding protein‐1 ( ρ = 0.67, P < 0.001). Current or past treatment with ritonavir‐boosted lopinavir (LPV/r) was associated with endothelial activation (odds ratio = 5.0, 95% CI: 1.7–17, P = 0.0020). Conclusions: Endothelial activation is prevalent in CLWH despite viral suppression with combination ART and is associated with intestinal epithelial injury, systemic inflammation and treatment with LPV/r.